2019
DOI: 10.1111/febs.15036
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of natural PCSK9 mutants in modern and archaic humans

Abstract: PCSK9 is the last member of the proprotein convertases (PCs) family and its gene is mutated in ~ 2% to 3% of individuals with familial hypercholesterolemia (FH). This protein enhances the degradation of the low‐density lipoprotein receptor (LDLR) and hence increases the levels of circulating LDL‐cholesterol (LDLc). Studies of the underlying mechanism(s) regulating the activity of different mutations in the PCSK9 gene are ongoing as they enhance our understanding of the biology and clinical relevance of PCSK9 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The reason why the lack of PCSK9 activity has not yet been associated with defined negative outcomes is surprising and begs the question of why PCSK9 was kept during mammalian evolution, but lost in some species, and very rarely in human. PCSK9 LOF variations reducing circulating LDLc levels might have been problematic for our ancestors, such as the hunter-gatherer Denisovans ( 285 ), who probably had a cholesterol-poor diet, but can now be particularly advantageous for people on cholesterol-rich diets, such as those living in industrialized countries. In fact, it has been suggested that in some placental mammalian species PCSK9 underwent “pseudogenization” leading to the loss of active full length PCSK9 protein ( 286 , 287 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reason why the lack of PCSK9 activity has not yet been associated with defined negative outcomes is surprising and begs the question of why PCSK9 was kept during mammalian evolution, but lost in some species, and very rarely in human. PCSK9 LOF variations reducing circulating LDLc levels might have been problematic for our ancestors, such as the hunter-gatherer Denisovans ( 285 ), who probably had a cholesterol-poor diet, but can now be particularly advantageous for people on cholesterol-rich diets, such as those living in industrialized countries. In fact, it has been suggested that in some placental mammalian species PCSK9 underwent “pseudogenization” leading to the loss of active full length PCSK9 protein ( 286 , 287 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue-specific PCSK9 KO in mouse small intestine ( 146 ), pancreatic β-cells ( 47 ), and lung epithelia ( 128 ) allowed some dissection of the relationship between the autocrine and endocrine functions of PCSK9 but clearly emphasized the dominant role of circulating PCSK9 originating from liver ( 48 , 80 ). Furthermore, the intracellular activity of PCSK9 found in cell lines ( 73 ) seems distinct from that of circulating PCSK9 ( 148 , 149 ) and may play important roles during embryonic development ( 41 ) and in placenta ( 85 , 150 ), and possibly explain the GOF of some PCSK9 variants.…”
Section: Discussionmentioning
confidence: 99%
“…Ancient humans were hunter-gatherers likely living on hunted fowl and berries. 26 Denisovan and Neanderthal sequencing revealed unique PCSK9 mutations predicted to result in loss-of-function alleles. 26 Loss-of-function variants of PCSK9 may have been tolerated if dietary lipid was in abundance but might have been disadvantageous to human ancestors who had to survive long periods of lipid-poor meals.…”
Section: Genetic Diversity and Domesticationmentioning
confidence: 99%
“…26 Denisovan and Neanderthal sequencing revealed unique PCSK9 mutations predicted to result in loss-of-function alleles. 26 Loss-of-function variants of PCSK9 may have been tolerated if dietary lipid was in abundance but might have been disadvantageous to human ancestors who had to survive long periods of lipid-poor meals. 13,26 Our fundamental understanding of genetic selection stipulates that while a few rare families have loss-of-function alleles of PCSK9, which serve to protect them from cardiovascular disease, the wild-type protein has important functions precisely because it has remained functional under selective pressure for over 350 million years throughout vertebrate evolution from fishes to humans.…”
Section: Genetic Diversity and Domesticationmentioning
confidence: 99%
See 1 more Smart Citation